Income elasticity of demand for tanning bed usage: Evidence from survey data - Neil R. Meredith; Anne Marie Macy; Amy Meredith (Journal of Applied Economics, 2022)
Using data on U.S. adults from the National Health Interview Survey (NHIS), we estimate the causal income elasticity of tanning bed usage conditional upon use. While controlling for individual characteristics, we employ instrumented probit and count data estimation to show that tanning bed usage is a normal good that is a necessity for all adults, women and men alike. Results suggest an income elasticity magnitude of 0.823 for all adults, which implies that a 10 percent increase in instrumented income increases tanning bed usage by 8.23 percent. When examining 18-25 year olds, the magnitude increases to 1.563-a 10 percent increase in instrumented income causes a 15.63 percent increase in tanning bed usage. The findings add to research on health behaviors and suggest that policymakers wanting to discourage tanning bed usage may have to tax consumption considerably or enhance public health campaigns to prevent and curb usage.
Keywords: 330; Affordable Care Act; Elasticity; health; tanning bed